A Balancing Act : Reform Options for Paraguay's Fiscal Responsibility Law - David, Antonio (IMF Working Papers; Working Paper, 2016)
Paraguay faces a trade-off between building fiscal credibility and amending the existing fiscal rule to accommodate infrastructure investment and provide space for countercyclical policies. In this paper, we discuss several alternative fiscal rules for Paraguay and present simulations of debt trajectories in each case, assuming a baseline and three deterministic shock scenarios. We provide a supplementary Excel file to replicate debt simulations under different fiscal rules. The results suggest that potential modifications to make the fiscal rules more flexible in Paraguay should be accompanied by a number of safeguards that enhance credibility of the fiscal anchor and preserve sustainability.